2015
DOI: 10.1177/0273475315586596
|View full text |Cite
|
Sign up to set email alerts
|

Update Status

Abstract: The purpose of this research is to examine how the topic of social media has been integrated and executed within academic institutions and marketing courses. An exploratory survey of marketing educators that taught social media in their course(s) was undertaken. The survey addressed how social media was embedded within an institute's curriculum, the amount of coverage given to social media, teaching approach taken, what specific topics were covered, instructional materials, type(s) of assessment, and unique pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…The pressures arising for marketing educators from the demand to remain current and informed by the needs of industry have been noted (Mintu-Wimsatt & Lozada, 2018;Muñoz & Wood, 2015;Spiller & Tuten, 2019). There are systemic barriers, given that success in academia is largely defined in terms of research (knowing), and career progression is tied to innovative research which often involves developing expertise in a narrow and theoretical field.…”
Section: Implications For Marketing Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…The pressures arising for marketing educators from the demand to remain current and informed by the needs of industry have been noted (Mintu-Wimsatt & Lozada, 2018;Muñoz & Wood, 2015;Spiller & Tuten, 2019). There are systemic barriers, given that success in academia is largely defined in terms of research (knowing), and career progression is tied to innovative research which often involves developing expertise in a narrow and theoretical field.…”
Section: Implications For Marketing Educationmentioning
confidence: 99%
“…Another set of barriers related to practice-informed, holistic teaching pertains to resource constraints. The greatest challenge for marketing educators is the time and effort required to stay current (Muñoz & Wood, 2015). Within the subject of analytics, there is a considerable lack of knowledge and skills among existing marketing faculty as most undertook their academic training before the advent of big data and thus lack both the expertise and interest in integrating the subject with their teaching (Liu & Burns, 2018;Mintu-Wimsatt & Lozada, 2018).…”
Section: Implications For Marketing Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our students, often digital natives, are seen as coming into SM marketing courses and SM manager positions armed with general knowledge and intuition relating to SM. Logically, this knowledge is only related to usage as a consumer , as instructors often recognize gaps in their knowledge, especially in strategic planning and analytics (Muñoz and Wood 2015). Usage, strategic planning, and analytics are only part of what is needed to navigate SM's impact on its users and the business world.…”
Section: Sm Wellness: Warrants Marketing Attentionmentioning
confidence: 99%
“…When social media marketing education was explored in a special issue in 2015, the research showed social media marketing in the classroom was still in its infancy (Brocato et al, 2015). These authors, along with Muñoz and Wood (2015), called for future research to focus on how educators can facilitate training in the classroom to align with skills desired by practitioners. This discussion returns to a debate we have seen in marketing education literature for some time: How should universities balance teaching more conceptual-based knowledge versus technical skills (Pefanis Schlee & Harich, 2010; Schibrowsky et al, 2002) and what classroom assessments best help facilitate both knowledge and skill development?…”
mentioning
confidence: 99%